2010
DOI: 10.1614/wt-d-10-00029.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safening of Aryloxyphenoxypropionate Herbicides when Tank-Mixed with Triclopyr for Bermudagrass Control in Zoysiagrass Turf

Abstract: Aryloxyphenoxypropionate (AOPP) herbicides are used to control bermudagrass contamination in various turfgrasses. Applying AOPP herbicides alone can cause unacceptable injury to zoysiagrass but injury can be reduced when tank-mixed with triclopyr. There are limited data illustrating the extent of bermudagrass control and zoysiagrass cultivar tolerance when these compounds are combined. Research was conducted to determine the efficacy of multiple AOPP herbicides applied alone and tank-mixed with triclopyr for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
51
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 16 publications
14
51
1
1
Order By: Relevance
“…Visual hybrid bermudagrass injury data were more closely correlated to assessments of turfgrass cover on all dates; additionally, the greatest degree of association was observed in data collected 3 WAT regardless of parameter. These findings support those of Lewis et al (2010) and Yelverton et al (2009), who also observed no advantages in using DIA in place of visual ratings for assessing herbicide responses in turf.…”
Section: Resultssupporting
confidence: 90%
“…Visual hybrid bermudagrass injury data were more closely correlated to assessments of turfgrass cover on all dates; additionally, the greatest degree of association was observed in data collected 3 WAT regardless of parameter. These findings support those of Lewis et al (2010) and Yelverton et al (2009), who also observed no advantages in using DIA in place of visual ratings for assessing herbicide responses in turf.…”
Section: Resultssupporting
confidence: 90%
“…For example, this might be the case when maintaining a more tolerant cultivar such as Geo zoysiagrass, or when short‐term injury or reductions in quality are not a major concern, such as on a sod farm. However, it is noteworthy that besides injury reduction, triclopyr as a broadleaf herbicide also broadens the weed control spectrum of a single application; moreover, mixtures of triclopyr with certain AOPP herbicides including fluazifop‐P‐butyl have been found to improve bermudagrass suppression compared with using an AOPP herbicide alone (McElroy and Breeden, 2006; Doroh et al, 2010; Lewis et al, 2010). Brosnan et al (2011) reported early spring and fall to be the seasons during which greatest bermudagrass injury was observed and proposed that greater absorption and translocation rates may be the cause.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in response to triclopyr alone could be cultivar specific, as zoysiagrass cultivars have demonstrated diversity regarding herbicide susceptibility and recovery rate (Flessner et al, 2011b; Leon et al, 2014). For example, within Z. matrella , ‘Diamond’ is highly susceptible to AOPP herbicides, and triclopyr does not exhibit a safening effect (Lewis et al, 2010). Conversely, as shown here, Zeon is also susceptible, but exhibited a clear safening response to triclopyr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, triclopyr, a pyrimidine carboxylic acid herbicide, can increase zoysiagrass (Zoysia japonica Steud.) tolerance to AOPP herbicides (Doroh et al 2010;Lewis et al 2010;McElroy and Breeden 2006).…”
mentioning
confidence: 99%